if alpha(@) and beta are zeroes of the polynomial x square -5x+k such that alpha(@)-beta=1. find the value of k
Answers
Answered by
8
Heya here ...☺☺
Solution is given below.
_____________________________
By using the relationship between the zeros of the Polynomial
we have -
![sum \: \: of \: \: zeroes = \frac{ - (coefficient \: \: of \: x)}{coefficient \: \: of \: {x}^{2} } \\ \\ product \: \: of \: zeroes = \frac{constant \: \: term}{coefficient \: \: of \: {x}^{2} } \\ \\ = > \alpha + \beta = \frac{ - ( - 5)}{1} \: \:and \: \: \: \alpha \beta = \frac{k}{1} \\ \\ solving \: \: \: \alpha - \beta = 1 \: \: and \: \\ \alpha + \beta = 2 \\ \\ we \: get \: \: \\ \alpha = 3 \: \: \: \: and \: \: \: \beta = 2 sum \: \: of \: \: zeroes = \frac{ - (coefficient \: \: of \: x)}{coefficient \: \: of \: {x}^{2} } \\ \\ product \: \: of \: zeroes = \frac{constant \: \: term}{coefficient \: \: of \: {x}^{2} } \\ \\ = > \alpha + \beta = \frac{ - ( - 5)}{1} \: \:and \: \: \: \alpha \beta = \frac{k}{1} \\ \\ solving \: \: \: \alpha - \beta = 1 \: \: and \: \\ \alpha + \beta = 2 \\ \\ we \: get \: \: \\ \alpha = 3 \: \: \: \: and \: \: \: \beta = 2](https://tex.z-dn.net/?f=sum+%5C%3A++%5C%3A+of+%5C%3A++%5C%3A+zeroes+%3D++%5Cfrac%7B+-+%28coefficient+%5C%3A++%5C%3A+of+%5C%3A+x%29%7D%7Bcoefficient+%5C%3A++%5C%3A+of+%5C%3A++%7Bx%7D%5E%7B2%7D+%7D++%5C%5C++%5C%5C+product+%5C%3A++%5C%3A+of+%5C%3A+zeroes+%3D++%5Cfrac%7Bconstant+%5C%3A++%5C%3A+term%7D%7Bcoefficient+%5C%3A++%5C%3A+of+%5C%3A++%7Bx%7D%5E%7B2%7D+%7D++%5C%5C++%5C%5C++%3D++%26gt%3B++%5Calpha++%2B++%5Cbeta++%3D++%5Cfrac%7B+-+%28+-+5%29%7D%7B1%7D++%5C%3A++%5C%3Aand+%5C%3A+++%5C%3A++%5C%3A++%5Calpha++%5Cbeta++%3D++%5Cfrac%7Bk%7D%7B1%7D+%5C%5C+++%5C%5C+solving+%5C%3A+++%5C%3A++%5C%3A+%5Calpha++-++%5Cbeta++%3D+1+%5C%3A++%5C%3A+and+%5C%3A++%5C%5C++%5Calpha++%2B++%5Cbeta++%3D+2+%5C%5C++%5C%5C+we+%5C%3A+get+%5C%3A++%5C%3A++%5C%5C++%5Calpha++%3D+3+%5C%3A++%5C%3A++%5C%3A++%5C%3A+and+%5C%3A++%5C%3A++%5C%3A++%5Cbeta++%3D+2)
substituting these values in αβ = Κ/1,
we get
The value of k = 6
_____________________________
HOPE it's helps you.
Solution is given below.
_____________________________
By using the relationship between the zeros of the Polynomial
we have -
substituting these values in αβ = Κ/1,
we get
The value of k = 6
_____________________________
HOPE it's helps you.
Anonymous:
Nice answer sis
Answered by
2
Answer:
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/dd2/084d47314cf6e2e9873e4581451b0837.jpg)
Similar questions